PERKEMBANGAN KELIMPAHAN FITOPLANKTON DENGAN PEMBERIAN PUPUK ORGANIK CAIR - Niken Ayu Pamukas (Berkala Perikanan Terubuk, 2011)
Phytoplankton is a very important microorganisms in pond, it has a function asprimary producer, natural fish food and as supporting water quality parameters.Phytoplankton growth could be supported by adding fertilizer. One of the best fertilizerthat could be used is liquid organic fertilizer. This research was conducted on June 1-28,2009 at the Water Quality Management Laboratory, Faculty of Fisheries and MarineScience, University of Riau. The aim of this research was to investigate the effect ofaddition of liquid organic fertilizer toward phytoplankton abundance. Completerandomly design with one factor, six treatments and three replications was applied. Resultshowed that positive relationship between concentrations of liquid organic fertilizer andphytoplankton abundance. Liquid organic fertilizer concentrations applied were : P0(Control), P1 (0,133 ml/m3), P2 (0,244 ml/m3), P3 (0,511 ml/m3), P4 (1,00 ml/m3) and P5(2,00 ml/m3). Result showed that the best abundance was obtained from P5 (2,00 ml/m3)with phytoplankton abundance was 21667 ind/l. The organic material of soil content from3,820-8,631 %, nitrate concentration 0,234-2,605 ppm, temperature 24-320C, pH of water(6,1-7,9), DO 3,0-5,3 ppm, turbidity 38-228 NTU, CO2 11,99-50,40 ppm andorthoposphate concentration 0,099-0,427 ppm.